Determinants of Revascularization Success in STEMI Patients - Serhii S. Shpak; Sergii V. Salo; Valentyn O. Shumakov; Anastasia Kiriluk (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Immediate angiographic outcomes after stenting of the infarct-related artery in STEMI patients are important predictors of long-term outcomes such as survival, risk of severe heart failure, or left ventricular aneurysm formation. These outcomes can be assessed using the Thrombolysis in Myocardial Infarction (TIMI) flow grade. The lower the score, the higher the associated mortality rate. Understanding the factors that may influence the outcome of revascularization is crucial.Aim. To demonstrate the determinants influencing the success of PCI.Materials and Methods. Between 2022 and 2024, the study included 160 STEMI patients who underwent PCI. Specific correlation tests were applied for statistical analysis.Results. Time to hospital admission emerged as one of the most critical determinants of successful PCI. Among all identified correlations, the most significant were the following: elderly patients had a higher likelihood of multivessel coronary artery disease; patients with diabetes mellitus were more likely to experience prolonged acute ischemia and had a higher incidence of cardiogenic shock.Conclusions. Patients with prolonged acute ischemia more often present with subocclusion rather than total occlusion. Diabetic patients tend to seek medical care later, often presenting with myocardial infarction complications, and are more likely to develop cardiogenic shock. Thromboaspiration and predilatation are associated with impaired TIMI flow in PCI of the infarct-related artery.